Enhancing Cloud Data Security with Identity-Based Remote Data Integrity Checking - Kondragunta Rama Krishnaiah (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In cloud computing environments, ensuring the integrity of remotely stored data is crucial for maintaining security and privacy. Traditional Remote Data Integrity Checking protocols, while effective, often suffer from high computational overhead and complex key management systems. This paper proposes a novel Identity-Based Remote Data Integrity Checking protocol that leverages Identity-Based Cryptography to simplify key management, reduce computational overhead, and improve scalability in cloud storage systems. Our approach involves three key entities: the Cloud User, Cloud Server, and Third-Party Auditor, with the TPA responsible for periodically verifying data integrity without accessing the actual content of the data. We conduct extensive experiments to evaluate the system’s performance, including data upload, metadata generation, and integrity verification times. The results demonstrate that the IB-RDIC protocol offers significant improvements in computational efficiency and scalability compared to traditional Public Key Infrastructure -based systems. The system incurs lower computational and storage overhead, while maintaining strong data integrity protection and privacy preservation. Furthermore, the proposed protocol is more efficient than existing RDIC protocols such as Provable Data Possession and Proof of Retrievability, making it a promising solution for modern cloud storage environments. Finally, we discuss potential future improvements and the practical deployment of the Identity-Based Remote Data Integrity Checking protocol in real-world cloud applications.